TRANSISTOR FILM TIPIS ORGANIK BERBASIS POLIANILIN UNTUK APLIKASI SENSOR GAS AMONIAK - Taofik Jasa Lesmana (Jurnal Biofisika, 2013)
Thin-film  transistor  has been  fabricated  by  chemical  deposition  of polyaniline  on top of  the SiO2  dielectric  layer.  Thin-film  transistors  made  electrically  tested  to  see  the effects  of  terrain  characteristics  and  sensitivity  to  ammonia  gas.  Negative  gate voltage  is  supplied  to  the  transistor  polyaniline  increases  the  drain  current  flowing. Polyaniline  transistor  drain  current  decreased  when  ammonia  gas  is  given  which shows that the NH3 molecules reduce the carrier mobility in polyaniline